Relationship Between the Types and Diameters of Residual Vessels and Secondary TAPS after Fetoscopic Laser Surgery for TTTS - Feng, Shuo; Li, Genxia; Yin, Pan; Zhu, TeXuan; Cheng, ChunHua; Dong, Li (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Objective This study aimed to investigate the relationship between the characteristics and diameters of residual anastomoses and the occurrence of twin anemia-polycythemia sequence (TAPS) in twin-to-twin transfusion syndrome (TTTS) patients with placental vascular injection after fetoscopic laser surgery (FLS).Methods A total of 90 cases of pregnant women who underwent FLS owing to TTTS were collected in the university hospital from May 2018 to December 2020. Therein, 40 cases received placental injection and were divided into the TAPS group and non-TAPS group according to the postoperative complications. The number of residual superficial anastomoses was counted and the diameter was measured.Results Among the placentae of nine patients in the TAPS group, two cases had no superficial anastomoses, and seven cases had 16 superficial anastomoses, including eight arterio-venous (AV) anastomoses, two veno-arterial (VA) anastomoses, three arterio-arterial (AA) anastomoses and three veno-venous (VV) anastomoses. Among the placentae of 31 patients in the non-TAPS group, 19 cases had no superficial anastomoses, and 12 cases had 18 superficial anastomoses, including two AV anastomoses, five VA anastomoses, seven AA anastomoses, and four VV anastomoses; and both the two cases of AV anastomoses were accompanied by AA anastomoses. The number of AV anastomoses in the placentae of the TAPS group was significantly elevated compared with that in the non-TAPS group (p<0.05). While there was no significant difference in the numbers of placentae with superficial anastomoses, the numbers of blood vessels with VA anastomoses, VV anastomoses, and AA anastomoses between the two groups (p>0.05). Through analyzing the diameters of 34 superficial anastomoses in the two groups, it was shown that the diameters of AA anastomoses in the non-TAPS group were significantly larger than those in the TAPS group (Z=1.97, p<0.05). There was no statistical difference in the diameters of AV anastomoses (Z=0.52, p>0.05), VA anastomoses (Z=0.98, p>0.05), and VV anastomoses (Z=0.36, p>0.05). The differences of the birth weight and inter-twin hemoglobin difference were statistically significant (p<0.05). The result indicated that the differences between age, gestational weeks at operation, delivery, and mean operating times were not statistically significant (p>0.05).Conclusion The increase in the number of AV anastomoses could obviously elevate the incidence of TAPS. The probability of TAPS occurrence is reduced following the increased diameters of AA anastomoses, demonstrating that AA anastomosis has a protective effect on TTTS patients.
Keywords: twin-to-twin transfusion syndrome; twin anemia-polycythemia sequence; fetoscopic laser surgery; residual anastomoses